KOMUNIKASI ORANG TUA PADA ANAK PENDERITA AUTISME: LITERATUR REVIEW - Fariz Ryan Maulana; Dini Nur Alpiah (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Autism spectrum disorders (ASD) pose significant challenges in communication and social interaction, affecting affected individuals and their families. Understanding how parents communicate with their autistic children is critical to providing effective support and intervention to improve the quality of life for these individuals. This study aims to explore the communication strategies used by parents in interacting with their children diagnosed with autism, highlighting the significance of parental communication in responding to the needs of autistic individuals. A comprehensive literature review was conducted to gather insights from five relevant studies that focused on parental communication in the context of autism. These studies use qualitative methods such as case studies, interviews, observations, and document analysis to investigate various aspects of parents' communication with autistic children. Findings emphasize the important role of parental communication in the management and development of children with autism. Effective communication strategies, including interpersonal communication styles, openness, empathy, and positive reinforcement, were identified as important elements in facilitating meaningful interactions between parents and their autistic children. Additionally, these studies emphasize the importance of collaboration between parents, educators, health professionals, and the general public in creating a supportive environment for autistic individuals. This research highlights the critical role of parental communication in supporting the social and emotional well-being of children with autism. Further research is needed to deepen our understanding of the complexity of autism and to develop comprehensive interventions and support programs that address the diverse needs of autistic individuals and their families. Additionally, educational initiatives aimed at increasing parents' and educators' knowledge about autism and effective communication strategies are essential to building inclusive environments and maximizing the potential of individuals with autism.